P249 Quality improvement project for cross site hepatopancreaticobiliary/interventional referrals. (19th June 2022) - Akram, Ali; Ahmed, Salman; Galloway, Daniel; Collins, Carole; Benson, Martin
Abstract : Introduction: Chelsea and Westminster Hospital (C&W) Gastroenterology department currently provides interventional endoscopy/HPB services across West Middlesex, Royal Brompton, Royal Marsden and C&W Hospital sites. Historically referrals were made through multiple modes of communications e.g. Cerner, Gastro Spr bleep, phone, WhatsApp or email to individual NHS addresses. We had identified challenges in this practice in regards to vetting, planning and prioritizing the urgent cases. With the current practice there was no robust system in place to identify patients needing repeat procedure or follow up intervention. Methods: We formulated a single platform to receive all intervention/HBP referrals from all sites to facilitate vetting, prioritising and organising pre-procedure investigations in a timely way, such a platform would help to utilize GA list slots to its maximum potential. We had identified referrals for patients who waited longer to get a slot as initial referrals had been sent to rotational doctors who were no longer working in Chelsea Hospital. After discussion with lead consultants we requested IT department set up a new generic email I.D which can be accessed by the appropriate staff members and developed a uniform referral system in our trust. chelwest.interventionalendoscopy@nhs.net was introduced in October 2021 along with a new referral form which required the referring team to provide all the essential information deemed necessary for the preparation and procedure planning. This included not only current presentation and medical background, blood results and imaging but also COVID status, infection risk, anticoagulation and performance and consent status. Results: We received excellent informal and then formal feedback from endoscopy staff, gastroenterology and anaesthetic colleagues for the changes we implemented for referrals which made our lists run smoothly and efficiently. The endoscopy team has been able to promptly book patients for any empty slots, organize their bloods, Covid swabs or other investigations required for procedures including admissions. Anaesthetic team has been able to identify high risk cases and ask for required pre-procedure investigations thereby improving patient safety and minimising last minute cancellations. We have performed 7 more interventional procedures in November 2021 as compare to November 2020 after implementation of our changes. Conclusion: The above mention QIP has significantly improved in our HPB service making it more cost effective efficient to plan and run interventional list smoothly. To conclude we should use single platform for intervention/HPB referrals for HPB centres to improve endoscopy service.